A case of successfully treated recalcitrant EGFR inhibitor‐induced acneiform eruption following non‐ablative fractional laser. Issue 4 (5th May 2016) - Choi, Joong Woon; Kim, Tae In; Jeong, Ki‐Heon; Shin, Min Kyung
Abstract: Epidermal growth factor receptor (EGFR) inhibitor, a targeted therapy in the field of oncology, is a new drugs suggested for the cause of acneiform eruptions. The unresponsiveness to conventional acne therapy is a pivotal reason of seeking alternatives to treat drug‐induced acneiform eruptions. A 30‐year‐old female treated with cetuximab, EGFR inhibitor presented with numerous sized erythematous papules and pustules on her face. All responses of oral medications and topical application were poor. She was treated with two passes of non‐ablative 1550 nm fractional erbium glass laser with topical clindamycin. After three laser sessions, the skin lesions improved dramatically without any side effects. There is currently no single effective treatment for acneiform eruption. This report shed light on the possibility that non‐ablative fractional laser can be an alternative for recalcitrant drug‐induced acneiform eruptions.